In memoriam: Sasan Aliniaeifard (1981 – 2025) - Javadi Asayesh, Elahe; Sobhani, Mohammadhadi; Malcolm Matamoros, Priscilla; Li, Tao; Marcelis, Leo F. M.; Woltering, Ernst; Kaiser, Elias (Frontiers in Plant Science, 2025)
We celebrate the life and mourn the untimely passing of Dr. Sasan Aliniaeifard, an inspiring scientist, teacher, entrepreneur and mentor, who contributed to the science of controlled environment agriculture (CEA) in Iran and beyond.